Frequency of Lower Urinary Tract Injury after Gastrointestinal Surgery in the Nationwide Inpatient Sample Database. Issue 12 (December 2014) - Sawkar, Hari P.; Kim, Dae Y.; Thum, D. Joseph; Zhao, Lee; Cashy, John; Bjurlin, Marc; Bhalani, Vishal; Boller, Anne-Marie; Kundu, Shilajit
Bladder and ureteral injury are serious iatrogenic complications during abdominal and pelvic surgery but are poorly investigated in the general surgery literature. The objective of this study was to examine rates, trends, and patient and surgical characteristics present in lower urinary tract injuries during gastrointestinal surgery using the Nationwide Inpatient Sample (NIS) database. The NIS database was queried from 2002 to 2010 for gastrointestinal surgery procedures including small/large bowel, rectal surgery, and procedures involving a combination of the two. These were crossreferenced with bladder and ureteral injury using International Classification of Diseases, 9th Revision, Clinical Modification codes. Multivariate regression analysis was used to calculate odds ratios for hypothesized risk factors. From 2002 to 2010, total average rates of bladder injury and ureteral injury were 0.15 and 0.06 per cent, respectively. Small/large bowel procedures had lower annual rates of ureteral (0.05 to 0.07%) and bladder (0.12 to 0.14%) injuries compared with ureteral (0.11 to 0.25%) and bladder (0.27 to 0.41%) injuries in rectal procedures. Presence of metastatic disease was associated with the greatest risk for bladder (odds ratio, 2.0; 95% confidence interval, 1.8 to 2.2) and ureteral (2.2; 1.9 to 2.5) injury in small/large bowel surgery, and for bladder (3.1; 2.5 to 3.9) and ureteral (4.0; 3.2 to 5.0) injury in combination procedures. Injury rates were significantly greater in open surgeries compared with laparoscopic procedures for both bladder injury (0.78 vs 0.26%, P < 0.0001) and ureteral injury (0.34 vs 0.06%, P < 0.0001). The incidence of genitourinary (GU) injury in gastrointestinal surgery is rare, less than 1.0 per cent, and is less than the incidence of GU injury reported in gynecologic surgery. This risk is increased by operations on the rectum and the presence of malignancy.